Amazing Grace - Hoffman, Mary, 1945-; Binch, Caroline (New York : Scholastic Inc., 1991)
Although a classmate says that she cannot play Peter Pan in the school play because she is black, Grace discovers that she can do anything she sets her mind to do.
Reprint: Originally published: New York : Dial Books for Young Readers, c1991.
"First Scholastic printing, September, 1993"--Verso t.p.